Bactericidal and synergistic activity of double-carbapenem regimen for infections caused by carbapenemase-producing Klebsiella pneumoniae. (February 2016) - Oliva, A.; Gizzi, F.; Mascellino, M.T.; Cipolla, A.; D'Abramo, A.; D'Agostino, C.; Trinchieri, V.; Russo, G.; Tierno, F.; Iannetta, M.; Mastroianni, C.M.; Vullo, V.
Abstract: Available therapeutic options against carbapenem-resistant Klebsiella pneumoniae (CR-Kp) are limited because of the high level of resistance to other antimicrobial classes including polymyxins. The double-carbapenem regimen has been recently considered a possible therapeutic strategy. In the present study, we evaluated the in vitro bactericidal and synergistic activity of a double-carbapenem regimen consisting of ertapenem plus high-dose meropenem in a series of patients with healthcare-associated CR-Kp infections in whom the use of colistin was not indicated because of potential nephrotoxicity and/or resistance. In vitro synergy was evaluated using checkerboard and killing studies. A total of 15 patients were included in the study, with sepsis, severe sepsis and septic shock found in two (13.3%), five (33.3%) and one (6.7%) patients, respectively. Overall, the clinical/microbiological response was 12/15 (80%). Synergy was observed in 11/14 (78.6%) isolates using the checkerboard method whereas in killing studies 12/14 (85.7%) and 14/14 (100%) strains were synergistic and bactericidal at 24 h at concentrations of 1 × MIC MEM + 1 × MIC ERT and 2 × MEM + 1 × MIC ERT, respectively, with a significant decrease of log CFU/mL compared with other combinations (p <0.0001). The double-carbapenem regimen showed clinical and in vitro effectiveness in patients with CR-Kp infections.